Aerodynamics of leading-edge protection tapes for wind turbine blades. Issue 5 (October 2021) - Major, Desirae; Palacios, Jose; Maughmer, Mark; Schmitz, Sven
This paper presents results of a comparative study on the effect of standard and tapered leading-edge protection (LEP) tapes on the annual energy production (AEP) of a utility-scale 1.5 MW wind turbine. Numerical models are developed in STAR-CCM+ to estimate the impact of LEP tapes on lift and drag coefficients of an NACA 64-618 airfoil operating at Re = 3 × 10 6 . Experimental drag coefficient data are collected for LEP tapes applied to the tip-section of a de-commissioned wind turbine blade for numerical validation. The objective is to determine the physical mechanisms responsible for the aerodynamic degradation observed with standard LEP tapes, and to design a tapered LEP tape that reduces the associated adverse impact on AEP. An in-house wind turbine design and analysis code, XTurb-PSU, is used to estimate AEP using airfoil data obtained by STAR-CCM+. For standard LEP tapes, laminar-to-turbulent boundary-layer transition occurs at the LEP tape edge, resulting in AEP losses of 2%–3%. Comparable tapered LEP tapes can be designed to suppress boundary-layer transition for backward-facing step heights below a critical value such that associated impact on AEP is negligible.